2018
DOI: 10.1002/ppap.201700200
|View full text |Cite
|
Sign up to set email alerts
|

Reduced HeLa cell viability in methionine‐containing cell culture medium irradiated with microwave‐excited atmospheric‐pressure plasma

Abstract: The mechanism underlying the death of cancer cells incubated in plasma‐activated medium (PAM) prepared by irradiation of culture medium with atmospheric‐pressure plasma is revealed by analyzing changes in the culture medium composition using liquid chromatography‐tandem mass spectrometry and nuclear magnetic resonance spectroscopy. The concentration of the essential amino acid methionine declined in microwave‐excited plasma‐irradiated medium, whereas, that of methionine sulfoxide increased due to oxidation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…However, so far, most of the studies have examined the loss of function of amino acids as nutrients. For example, methionine in medium was oxidized by LTP treatment 27 . Ringer’s lactate solution contains sodium chloride, potassium chloride, calcium chloride, and L-sodium lactate, and we have previously reported that the reaction products between plasma and L-sodium lactate were anti-tumor factors in PAL 17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, so far, most of the studies have examined the loss of function of amino acids as nutrients. For example, methionine in medium was oxidized by LTP treatment 27 . Ringer’s lactate solution contains sodium chloride, potassium chloride, calcium chloride, and L-sodium lactate, and we have previously reported that the reaction products between plasma and L-sodium lactate were anti-tumor factors in PAL 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is found that Met in proteins is highly susceptible to oxidation under oxidative stress. 15 19 As an antioxidant defense system, Met oxidation participates in regulation of protein stability 20 and cellular viability 21 through its own oxidation: Met is oxidized to form methionine sulfoxide(MetSO) by adding oxygen to its sulfur atom in the physiological environment. MetSO produced may easily be reduced back to Met by thioredoxin-dependent enzymes under catalysis of methionine sulfoxide reductase.…”
Section: Introductionmentioning
confidence: 99%
“…Met is not only a precursor in protein synthesis but also participates in many biochemical processes, ,,, such as glycogen and d -glucose formation, production of S -adenosylmethionine and Succinyl-CoA, biosynthesis of homocysteine, cysteine, and glutathione, metabolism of phosphatidylcholine and phospholipids, as well as cellular and DNA methylation. In addition, it is found that Met in proteins is highly susceptible to oxidation under oxidative stress. As an antioxidant defense system, Met oxidation participates in regulation of protein stability and cellular viability through its own oxidation: Met is oxidized to form methionine sulfoxide­(MetSO) by adding oxygen to its sulfur atom in the physiological environment. MetSO produced may easily be reduced back to Met by thioredoxin-dependent enzymes under catalysis of methionine sulfoxide reductase. , The impairment of this regulation is associated with many diseases such as lung disease, cancer, neurodegeneration (Alzheimer’s disease), and cardiovascular and cerebrovascular disease. , However, the regulation functions of methionine as an antioxidant are still not fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Different amino acid combinations and concentrations in different media may considerably affect CAP efficacy due to potential reactions with plasma‐activated reactive species. It was reported that cysteine and methionine mainly contribute to the activity attenuation of plasma‐activated Dulbecco's modified Eagle's medium (DMEM) at 22°C and 8°C [ 80 ] ; the concentration of the essential amino acid methionine declined in PAM, whereas that of methionine sulfoxide increased due to methionine oxidation, and this contributes to the reduced survival rate of HeLa cervical carcinoma cells [ 81 ] ; and adding 20 mM lysine in DMEM could significantly increase the antiglioblastoma capacity of PAM. [ 82 ] These suggest that amino acids such as methionine, cysteine, and lysine are potential confounding factors of plasma dose if PAM is considered, and their contributions and effects vary in the treatment of different types of cancers.…”
Section: Challenges For Precision Plasma Dosementioning
confidence: 99%